Pengembangan Aplikasi Konversi Video Digital Greyscale Menjadi Video Digital Berwarna Dengan Menggunakan Metode Global Image Matching - Widiantara, Ketut; Windu Antara Kesiman, Made; Gede Sunarya, I Made (Universitas Pendidikan Ganesha, 2013)
This research aims to design and implement an application that could convert a greyscale video into a colored video digital, easily and staining results were satisfactory. Input from the applications is greyscale video and color reference image, and the output of this application was a videocolored with shades of color that refers to the reference image input. This application was developed by using the method of Global Image Matching was implemented in the Java programming language environment with editor used NetBeans 7.2.1. On an application made there were three main processes that extract the video, the process of coloring, and render process. The extraction process was the process of breaking into the video and audio frames. Coloring process was a process that implements the Global Image Matching method, in which frame-frame extraction results would be coloring in this process. While the rendering process was the process of combining frames staining results with the extracted audio files into a videocolored. Based on test results, greyscale digital video conversion application to digital video color conversion process can be done very easily and quickly.